A study of mycobacterial transcriptional apparatus: identification of novel features in promoter elements. - Bashyam, M D (1996)
Our earlier studies on transcriptional signals of mycobacteria had revealed that (i) strong promoters occur less frequently in the slowly growing pathogen Mycobacterium tuberculosis H37Rv than in the fast-growing saprophyte M. smegmatis and (ii) mycobacterial promoters function poorly in Escherichia coli. We now present evidence that RNA polymerases of M. smegmatis, M. tuberculosis, and M. bovis BCG recognize promoter elements with comparable efficiencies. Analysis of these randomly isolated mycobacterial promoters by DNA sequencing, primer extension, and deletion experiments revealed that their -10 regions are highly similar to those of E. coli promoters, in contrast to their -35 regions, which can tolerate a greater variety of sequences, owing presumably to the presence of multiple sigma factors with different or overlapping specificities for -35 regions, as reported earlier for the Streptomyces promoters. A comparison of the -10 and -35 binding domains of MysA, HrdB, and RpoD (the principal sigma factors of M. smegmatis, Streptomyces aureofaciens, and E. coli, respectively) showed that all three sigma factors have nearly identical -10 binding domains. However, the -35 binding domains of the principal mycobacterial and streptomycete sigma factors, although nearly identical to each other, are vastly different from the corresponding region of the sigma factor of E. coli. Thus, the transcriptional signals of mycobacteria have features in common with Streptomyces promoters but differ from those of E. coli because of major differences in the -35 regions of the promoters and the corresponding binding domain in the sigma factor.